Optimization of Urban Spaces to Municipal Development (Case Bandar Abbas) - Razaghpoor, Hadi; Kamran, Amin; Zarei, Sana; Dirand, Hamed; Kameli, Mohsen (Ciência e Natura, 2015)
Cities have grown haphazardly and urban areas have expanded to several times their primary size in a short while or have developed in separate sections without planning, tightly and randomly. This issue has come to be known as dispersion pattern or Sprawl and is a source of many problems in developing and developed cities. Bandar Abbas has also had a haphazard growth in the recent years. This paper attempts to investigate horizontal and vertical congestion in different parts of the city as a grid and then tries to draw on entropic indices with a cellular view to assess the order and balance of this grid city. Also, the results are used to compare the physical-operational concentration of the city between 2014 and 2006. In the end, a table is formulated according to the results presenting approaches, policies and projects for maintaining a balance between different parts of the city.